PERAN KOMISI YUDISIAL DALAM MENGATUR PERILAKU HAKIM - Khoiruddin Manahan Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This paper will discuss the role of the Judicial Commission in regulating the behavior of judges, so the formulation of the problem in this paper is how the role of the Judicial Commission in regulating the behavior of judges considering the position of judges in Indonesia is law enforcement officers who occupy a fairly high position in law enforcement in Indonesia. . To answer this problem, the author will use a qualitative method by searching the literature that discusses the problems above to be analyzed in order to draw conclusions. The finding in this paper is that the emergence of the Judicial Commission which is an external oversight agency makes behavior more controlled and directed in order to judge and decide in the fairest way possible to the people seeking justice.